Relatório de Estágio Profissional "Ser Professor de Educação Física: desafios e alegrias" - André Freitas Franco (2019)
The present document presents a set of experiences lived throughout the Professional Internship, inserted in the 2nd Cycle of Studies, leading to the Master's degree in Physical Education Teaching in Elementary and High School Education, by Sport Faculty of the Porto University (Faculdade de Desporto da Universidade do Porto). This Professional Internship was held in the 2018/2019 school year at the Dr. Ângelo Augusto da Silva Elementary and High School (Escola Básica e Secundária Dr. Ângelo Augusto da Silva), located in the Autonomous Region of Madeira Island, under the guidance of a Faculty Advisor from Porto University. Through this document, I presente some experiences that I have been living throughout this experience, showing positive aspects and aspects to improve in the future. With regard to the division of the document, which is mainly segmented into five parts: 1) in the first part - Personal Framework - I give a brief intro of my life course and the way I approached the area of Physical Education; 2) in the second part - Functional Framework - I approach the internship, its community and some aspects related to my Internship Center and the core group; 3) in the third part - Professional Internship: A New World - I frame my arrival at school, the initial expectations and some moments that marked my walk in school as a trainee; 4) The fourth part - Management of the Educational Process - I use to address the various important factors to the teaching-learning process and contextualize with some moments of reflection; 5) The fifth part - Participation in the School-Community dimension - I present my reflections on the participation in the activities organized by the Physical Education group within the scope of the annual plan of activities and others organized by the internship core group; 6) In the Sixth and last part - Action-Research: A Study on Autonomy - my research on autonomy is presented at the Elementary and High School Dr. Ângelo Augusto da Silva, where I try to understand the importance that teachers give to autonomy and the way they work it in their class.